Continuing education and teacher’s professional development: narratives of experiences lived in a public school of Mato Grosso (Research, Society and Development, 2020)
The narratives that compose this paper started to be outlined from the scrutinizing of actions done in a public school of Mato Grosso in 2016. It was aimed before and precipitously to understand how the formation meetings were done in the range of the project Educator’s Room. What perspectives do these meetings present when considered the relations between continuing education and teacher’s professional development, authentic dialogues and experiences? In methodological terms it is based in Narrative Research, such as comprehended by Clandinnin and Connelly. Narrating here is conceived as telling stories capable of bringing new meanings to the experiences lived, narrated. From the peculiar incursion in that Saturday morning it was resulted the comprehension that in a very peculiar way, in due proportions, collectives of learning have been constituted in the school context, been fomented by public politics of the State of Mato Grosso. However, the impact of such encounters in the teacher’s professional development needs to be comprehended, therefore it can be said that it is needed to scrutinize what approaches followed in these meetings favored the becoming person and teacher.